Algorithm for the Use of Geoinformation Technologies for the Purpose of Geoecological Monitoring of Territorial Communities - Koshel, A.; Denysiuk, B.; Poltavets А. (Land Management, Cadastre and Land Monitoring, 2025)
The article discusses the role and capabilities of modern geoinformation technologies in the process of geo-ecological monitoring of territorial communities. The growth of anthropogenic pressure, climate change and active development of land resources necessitate the introduction of innovative tools for timely detection, analysis and forecasting of the state of the environment. Geoinformation systems ensure the integration of different types of spatial data, their modelling and rapid visualisation, which enables local authorities to make scientifically sound management decisions on the use of natural resources, spatial planning and environmental safety at the local level. The study analyses the main functional capabilities of geographic information systems, in particular spatial analysis, geostatistics, risk modelling and scenario forecasting. Particular attention is paid to the use of remote sensing of the Earth to assess the dynamics of natural processes such as soil degradation, changes in vegetation cover, water balance and pollution detection. Examples are given of the application of integrated geoinformation solutions in communities for monitoring land conditions, analysing environmental sustainability and monitoring compliance with environmental protection standards. The results of the study prove that the introduction of geoinformation technologies into the geo-ecological monitoring system is a key condition for improving the efficiency of natural resource management at the level of local communities. The use of integrated geospatial data allows for more accurate assessment of environmental threats and the development of sound sustainable development strategies. Thus, geoinformation systems serve as the basis for the creation of modern monitoring systems that meet the requirements of adaptive management in the environmental sphere. Keywords: geoinformation systems, geo-ecological monitoring, amalgamated territorial community, land resource management, land use planning, rational land use.